Parkinson’s LRRK2-G2019S risk gene mutation drives sex-specific behavioral and cellular adaptations to chronic variable stress - Guevara, Christopher A.; Alloo, Kumayl; Gupta, Swati; Thomas, Romario; del Valle, Pamela; Magee, Alexandra R.; Benson, Deanna L.; Huntley, George W. (Frontiers in Behavioral Neuroscience, 2024)
Anxiety is a psychiatric non-motor symptom of Parkinson’s that can appear in the prodromal period, prior to significant loss of midbrain dopamine neurons and motor symptoms. Parkinson’s-related anxiety affects females more than males, despite the greater prevalence of Parkinson’s in males. How stress, anxiety and Parkinson’s are related and the basis for a sex-specific impact of stress in Parkinson’s are not clear. We addressed this using young adult male and female mice carrying a G2019S knockin mutation of leucine-rich repeat kinase 2 (Lrrk2G2019S) and Lrrk2WT control mice. In humans, LRRK2G2019S significantly elevates the risk of late-onset Parkinson’s. To assess within-sex differences between Lrrk2G2019S and control mice in stress-induced anxiety-like behaviors in young adulthood, we used a within-subject design whereby Lrrk2G2019S and Lrrk2WT control mice underwent tests of anxiety-like behaviors before (baseline) and following a 28 day (d) variable stress paradigm. There were no differences in behavioral measures between genotypes in males or females at baseline, indicating that the mutation alone does not produce anxiety-like responses. Following chronic stress, male Lrrk2G2019S mice were affected similarly to male wildtypes except for novelty-suppressed feeding, where stress had no impact on Lrrk2G2019S mice while significantly increasing latency to feed in Lrrk2WT control mice. Female Lrrk2G2019S mice were impacted by chronic stress similarly to wildtype females across all behavioral measures. Subsequent post-stress analyses compared cFos immunolabeling-based cellular activity patterns across several stress-relevant brain regions. The density of cFos-activated neurons across brain regions in both male and female Lrrk2G2019S mice was generally lower compared to stressed Lrrk2WT mice, except for the nucleus accumbens of male Lrrk2G2019S mice, where cFos-labeled cell density was significantly higher than all other groups. Together, these data suggest that the Lrrk2G2019S mutation differentially impacts anxiety-like behavioral responses to chronic stress in males and females that may reflect sex-specific adaptations observed in circuit activation patterns in some, but not all stress-related brain regions.